2008
DOI: 10.1002/ange.200802714
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the 3,4,5‐Tridehydropyridinium Cation—An Aromatic σ,σ,σ‐Triradical

Abstract: Unterschiedliche Angriffspunkte: Studien zur Reaktivität des 3,4,5‐Tridehydropyridiniumkations mithilfe eines Fourier‐Transformations‐Ionencyclotronresonanz‐Massenspektrometers belegen, dass bei radikalischen Reaktionen zuerst über C3 Bindungen gebildet werden, bei nichtradikalischen Reaktionen über C3 oder C4 (siehe Schema). Das stärker Brønsted‐saure isomere Kation 2,4,6‐Tridehydropyridinium verhält sich anders, weil die meta‐Benz‐in‐Positionen weniger reaktiv sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…This was expected as previous studies have demonstrated that thiomethyl abstraction is a dominant reaction for many related charged mono-and biradicals (distonic ions). 5,11,12,35 Only a small amount of DMDS radical cation (1−14% relative abundance; Table 1) was observed. In sharp contrast, the four isomeric triradicals studied (4−7; Table 1) produce the DMDS radical cation as the major product (83−94% relative abundance; Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This was expected as previous studies have demonstrated that thiomethyl abstraction is a dominant reaction for many related charged mono-and biradicals (distonic ions). 5,11,12,35 Only a small amount of DMDS radical cation (1−14% relative abundance; Table 1) was observed. In sharp contrast, the four isomeric triradicals studied (4−7; Table 1) produce the DMDS radical cation as the major product (83−94% relative abundance; Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Monoradicals 5 , 6 , 7 , and 8 show major reaction products, with branching ratios at or near 100%, that are diagnostic [21] for the presence of a radical site, such as a H atom abstraction product for cyclohexane and tetrahydrofuran, I atom abstraction product for allyl iodide and SCH 3 abstraction product for dimethyl disulfide (see Tables 1 and 2). The same primary reactions were observed for the para -benzynes.…”
Section: Resultsmentioning
confidence: 99%
“…To gain additional insight into the hydrogen atom abstraction reactions of 8, another hydrogen atom donor, cyclohexane, was examined. In a previous study, [16] mono-and biradicals were found to react with cyclohexane solely by one and/or two hydrogen atom abstractions. Biradical 8 reacts with cyclohexane by addition (19 %), and by one (35 %) as well as two (46 %) hydrogen atom abstractions (Scheme 7; reaction efficiency = 18 %).…”
mentioning
confidence: 91%
“…[4b, 6] Instead, 11 behaves like an activated electrophilic alkyne and readily undergoes nonradical addition reactions, as observed in previous studies. [16] The main reactions of 11 with THF (CH 2 O abstraction (49 %) and H 2 O abstraction (36 %)), AI (addition (72 %)), DMDS (HSCH 3 abstraction (92 %)), and tBuNC (HCN abstraction (90 %)), are thought to occur via nonradical mechanisms and hence do not require uncoupling of the biradical electrons in the transition state. [16] Therefore, they are not expected to be dependent on the magnitude of DE ST .…”
mentioning
confidence: 99%
See 1 more Smart Citation